Noninvasive Prenatal Nucleic Acid Diagnostics of Down Syndrome - Vodicka, Radek; Vrtel, Radek; Böhmova, Jana; Kratochvilova, Romana; Dusek, Ladislav; Dhaifalah, Ishraq; Santavy, Jiri (IntechOpen, 2011)
None